A phase I/II study of osimertinib in EGFR exon 20 insertion mutation-positive non-small cell lung cancer. (December 2021) - Yasuda, Hiroyuki; Ichihara, Eiki; Sakakibara-Konishi, Jun; Zenke, Yoshitaka; Takeuchi, Shinji; Morise, Masahiro; Hotta, Katsuyuki; Sato, Mineyoshi; Matsumoto, Shingo; Tanimoto, Azusa; Matsuzawa, Reiko; Kiura, Katuyuki; et al.
Highlights: Osimertinib 80 mg showed limited efficacy for NSCLC with  EGFR  ex20ins mutations. The mutation type-specific concentration-dependency of osimertinibwas highlighted. This study proposes higher dose osimertinib for NSCLC with EGFR ex20ins mutations. Abstract: Objectives: Several preclinical data proposed a potential efficacy of osimertinib, a third-generation EGFR tyrosine kinase inhibitor, for EGFR exon 20 insertion ( EGFR ex20ins)-positive non-small cell lung cancer (NSCLC). However, reported case series and a retrospective study proposed controversial efficacy. The efficacy of osimertinib in EGFR ex20ins-positive NSCLC have not been well evaluated in prospective clinical trials. In this study, we performed a prospective, single-arm, multi-center, open-label, non-randomized phase I/II study to evaluate efficacy of osimertinib for EGFR ex20ins-positive NSCLC. Materials and methods: From August 2018 to January 2020, 14 NSCLC patients with EGFR ex20ins were enrolled, of whom 2 were excluded because they did not meet the inclusion criteria. Efficacy and safety of 80 mg osimertinib were evaluated. In addition, we performed a translational exploratory study to clarify the association of mutation type-specific drug sensitivity, osimertinib pharmacokinetic data, and clinical efficacy. Results: Of the evaluated patients, none experienced objective response, 7 experienced stable disease (58.3%), and 5 experienced disease progression (41.7%). The median progression free survival (PFS) was 3.8 months, and the median overall survival was 15.8 months. Interestingly, the exploratory study demonstrated statistically significant positive correlation between plasma osimertinib concentration/ in vitro IC50 ratio and PFS (R = 0.9912, P = 0.0001), highlighting the mutation type-specific concentration-dependent efficacy of osimertinib for EGFR ex20ins-positive NSCLC. Conclusions: Regular dose, 80 mg/day, of osimertinib has limited clinical activity in NSCLC patients with EGFR ex20ins. The translational study proposed the potential efficacy of higher dose osimertinib in a subgroup of EGFR ex20ins-positive NSCLC.